The relationship between culturally-driven self- construal and consumers’ comprehension of three styles of visual metaphors in print advertising - Zhong, Yue (2017)
As the advertising industry becomes a mature market, the advertising should not only consider about the consumer groups and the overseas markets, but also consider how to stand out from the similar competitors. As a result, creative message strategies are employed more often in print advertisements targeting various consumer markets. Advertisers not only perform innovative creative metaphorical messages in the domestic market, attempting to draw the attention of targeted ethnic consumer groups, but also in international markets with different cultural background. Visual metaphors are widely applied in the modern print advertising. Advertisers intend consumers to recognize the comparison and understand the metaphor. The research question of this study comes to whether the visual metaphors are appreciated by consumers in the print advertising. This study indicated three sets of hypotheses. The first set of hypotheses was used to analyze that the different appreciations of advertisements with Similes, Hybrids and Contextual Metaphors. The second set of hypothesis aimed to test whether the appreciation of the advertisement will be changed by the comprehension. The third set of hypotheses in the study wanted to analyze that interdependent self- construal audiences will appreciate visual metaphors more than independent self- construal audiences. Based on the hypotheses, this study applied computerized questionnaire as the research method. This study was based on the advertisements of one product category, cars, a kind of high-investment product. Due to the experience of the product, the age of participants was limited from 24 to 45, who not limited in a certain occupation and nationality. Participants’ interdependent and independent self-construal were measured by the Self- Construal Scale (SCS). And a single item 7 points Likert scale was used to measure the appreciation of advertisements and how easy or hard to comprehend the visual metaphors and understand the intended meaning. After analyzing the data, this study came into conclusions that Hybrids is the least appreciated type of metaphors in the car advertisements. Simile becomes the most appreciated metaphor of the car advertisements. This finding can help advertisers learn about which type of creative mean of expression can not only appreciate consumers but also to be unique among the similar product advertisements. In addition, this study found that fully understanding Simile and Hybrid can help to increase the appreciation of the advertisement. Fully comprehended Contextual Metaphor, in some ways, can reduce the appreciation of the advertisement. The finding indicated that advertisers should balance the creation and comprehension of the advertisements with visual metaphors, in order to ensure consumers receiving the accurate information of the products from the advertisements. For the perspective of self-construal, this study found that the nationality is not the only factor to effect the self-construal. In addition, without considering the element of metaphor types, the appreciation of the interdependent self-construal participants is higher than the independent self-construal’s on the same advertisements. In the last part of this study, there were several suggestions for the further research. Different people have different explanation about the same images. This study believed that there can exist other elements in the rhetorical images. In addition, this study only focused on monomial metaphors, which were the signaling of the target. And the source of the metaphors was achieved only by visual methods. Verbal expression method can be researched in the future. Moreover, this study has not analyzed the amount of cognitive elaboration, which evoked by the visual structure of a metaphor. In another word, the amount of thoughts and associations, which raised by a certain metaphor can be considered as a function of the spatial arrangement of the image.